2019
DOI: 10.1155/2019/6916189
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Diet on Nutritional Diarrhea Associated with Gut Microbiota in Weaning Piglets: A System Review

Abstract: Piglets experience severe growth challenges and diarrhea after weaning due to nutritional, social, psychological, environmental, and physiological changes. Among these changes, the nutritional factor plays a key role in postweaning health. Dietary protein, fibre, starch, and electrolyte levels are highly associated with postweaning nutrition diarrhea (PWND). In this review, we mainly discuss the high protein, fibre, resistant starch, and electrolyte imbalance in diets that induce PWND, with a focus on potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 194 publications
(222 reference statements)
1
55
1
1
Order By: Relevance
“…In the present study, the relative abundances of genera Clostridium and Terrisporobacter were also lower in the gut microbiota of weaned pigs fed GLU than in that of weaned pigs fed CON. Generally, spore-forming Clostridium strains are recognized as the primary cause of diarrhea in neonatal and weaned piglets [ 49 ]. Previous studies reported that the spores and toxins from C. difficile and C. perfringens originated during the lactation period induced high rates of diarrhea and mortality after weaning [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the relative abundances of genera Clostridium and Terrisporobacter were also lower in the gut microbiota of weaned pigs fed GLU than in that of weaned pigs fed CON. Generally, spore-forming Clostridium strains are recognized as the primary cause of diarrhea in neonatal and weaned piglets [ 49 ]. Previous studies reported that the spores and toxins from C. difficile and C. perfringens originated during the lactation period induced high rates of diarrhea and mortality after weaning [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the role of dietary fibre and CP content in the post-weaning piglet diet, the role of fat in piglet nutrition has received only limited attention. This gap in knowledge is surprising, given that the ability of piglets to digest fat is impaired during the immediate post-weaning period, especially in case of diarrhoea [ 202 ]. The fat source used in post-weaning piglet diets should therefore be easily digestible.…”
Section: Post-weaning Nutritional Strategies During the Acute Phasmentioning
confidence: 99%
“…Diet is one of the main factors capable of modulating the gut microbial profile; thus, several reviews dealing with the effects of post-weaning diets on microbiota have been published [10][11][12][13]. Feeding measures of the post-weaning phase should contribute to reducing the gap between the pre-and the post-weaning phases, and, focusing on the gut microbiota, these should promote and restore the intestinal microbial eubiosis which was lost with weaning [88].…”
Section: Post-weaning Dietmentioning
confidence: 99%
“…An efficient way of modulating the intestinal microbiota is to regulate the nutritional composition of the diet, including the content of protein, starch and fiber [12,110,111]. As for other mammals, it has been well established that the ratio and type of protein and fiber play a key role in the modulation of the gut microbiota, affecting the development and establishment of beneficial (lactic acid bacteria) or opportunistic/pathogenic bacteria, which, in turn, can affect the intestinal health of the host [112,113].…”
Section: Post-weaning Dietmentioning
confidence: 99%
See 1 more Smart Citation